NHS Health Check programme: a rapid review update. Issue 2 (16th February 2022) - Tanner, L; Kenny, RPW; Still, M; Ling, J; Pearson, F; Thompson, K; Bhardwaj-Gosling, R
Abstract : Objective: To update a rapid review published in 2017, which evaluated the NHS Health Check programme. Methods: An enlarged body of evidence was used to readdress six research objectives from a rapid review published in 2017, relating to the uptake, patient experiences and effectiveness of the NHS Health Check programme. Data sources included MEDLINE, PubMed, Embase, Health Management Information Consortium (HMIC), Cumulative Index of Nursing and Allied Health Literature (CINAHL), Global Health, PsycINFO, the Cochrane Library, NHS Evidence, Google Scholar, Google, ClinicalTrials.gov and the ISRCTN registry, Web of Science, Science Citation Index, The Cochrane Library, NHS Evidence, OpenGrey and hand searching article reference lists. These searches identified records from between January 1996 and December 2019. Screening, data extraction and quality appraisal using the Critical Appraisals Skills Programme checklists were performed in duplicate. Grading of Recommendations Assessment, Development and Evaluations was implemented. Data were synthesised narratively. Results: 697 studies were identified, and 29 new studies included in the review update. The number of published studies on the uptake, patient experiences and effectiveness of the NHS Health Check programme has increased by 43% since the rapid review published in 2017. However, findings from the original review remain largely unchanged. NHS Health Checks led to an overall increase in the detection of raised risk factors and morbidities including diabetes mellitus, hypertension, raised blood pressure, cholesterol and chronic kidney disease. Individuals most likely to attend the NHS Health Check programme included women, persons aged ≥60 years and those from more socioeconomically advantaged backgrounds. Opportunistic invitations increased uptake among men, younger persons and those with a higher deprivation level. Conclusions: Although results are inconsistent between studies, the NHS Health Check programme is associated with increased detection of heightened cardiovascular disease risk factors and diagnoses. Uptake varied between population subgroups. Opportunistic invitations may increase uptake.